Penerapan Hipnosis 5 Jari Terhadap Tingkat Kecemasan Pada Mahasiswa Yang Menyelesaikan Tugas Akhir di Universitas ‘Aisyiyah Surakarta - Rizki Ardhiya Permata; Sitti Rahma Soleman (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Background: Final year students must complete a final assignment or thesis, on a topic in a particular field. Students experience a lot of stress and anxiety during the process of compiling their final assignment. The prevalence of anxiety disorders in adolescents in Central Java was recorded at 7.71%, up 4.7% from 2013 to 2018. To overcome anxiety can be done with pharmacology or non-pharmacology. Five-finger hypnosis is one type of relaxation therapy that can reduce anxiety and tension. Objective: To determine the effect of 5-finger hypnosis on reducing anxiety at Universitas 'Aisyiyah Surakarta. Method: Using a pre-test-post-test design. Samples of two students who are working on their final assignment and experiencing moderate to severe anxiety levels. The HARS questionnaire was used to measure anxiety levels. Results: The level of anxiety before and after being given Five Finger Hypnosis was that Ms. R's anxiety changed from moderate to mild and Ms. M's anxiety changed from severe to moderate. Conclusion: There is an influence on the anxiety experienced by students who are completing their final assignments before and after being given Five (5) Finger Hypnosis at 'Aisyiyah University, Surakarta.